Optimization of rituximab for the treatment of DLBCL: increasing the dose for elderly male patients. (8th October 2017) - Pfreundschuh, Michael; Murawski, Niels; Zeynalova, Samira; Ziepert, Marita; Loeffler, M.; Hänel, Matthias; Dierlamm, Judith; Keller, Ulrich; Dreyling, Martin; Truemper, Lorenz; Frickhofen, Norbert; Hünerlitürkoglu, Ali‐Nuri; et al.
Summary: Male sex is associated with unfavourable pharmacokinetics and prognosis in elderly patients with diffuse large B‐cell lymphoma (DLBCL). We investigated higher rituximab doses for elderly male DLBCL patients. Elderly patients (61–80 years) received 6 cycles CHOP‐14 (cyclophosphamide, doxorubicin, vincristine and prednisone at 14‐day intervals) and were randomized to 8 cycles rituximab (males 500 mg/m 2, females 375 mg/m 2 ) every 2 weeks or according to an upfront dose‐dense schedule. In 268 (120 females, 148 males) no difference between the standard and the upfront dose‐dense rituximab schedule was found (3‐year PFS 72% vs. 74%; OS 74% vs. 77%; P  =   0.651). The 500 mg/m 2 dose of rituximab for male patients was associated with serum levels and exposure times slightly better than in females and a male/female hazard ratio of 0.9 for progression‐free survival (PFS) and 0.8 for overall survival. For elderly males, 500 mg/m 2 was not more toxic than 375 mg/m 2 rituximab, but improved PFS by 32.5% ( P  =   0.039), with a trend for a (30%) better overall survival ( P  =   0.076) in a planned subgroup analysis adjusting for International Prognostic Index risk factors. We conclude that the higher rituximab dose for elderly male patients abrogated the adverse prognosis of male sex without increasing toxicity. In the era of personalized medicine, sex‐specific pharmacokinetics and toxicities should be investigated for all drugs where these parameters impact on outcome.